Discontinuing Medication: Recurrence Risk Factors - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1992)
The results of antiepileptic drug discontinuation in epileptic children who were seizure free for at least 2 years are reported from the Services of Child Neurology and Psychology, Department of Neurology, Clinics Hospital University of Sao Paulo Medical School, Sao Paulo, Brazil.